Optimization of pump efficiencies with different pumps characteristics working in parallel mode. (November 2016) - Koor, M.; Vassiljev, A.; Koppel, T.
Abstract: This paper concentrates on an algorithm for the prediction of steady running variable speed pumps (VSPs) working in parallel to keep them running close to the best efficiency point (BEP) provided by the pump manufacturer. Special focus is on the pumps that have different efficiency and performance characteristics. The complex optimization task to maximize the total efficiency of the pump system and thereby minimize energy consumption was solved with the customized optimization software using the Levenberg–Marquardt algorithm (LMA). Three different theoretical scenarios were analyzed: with working pumps having identical, slightly and largely different characteristics. The transition curves are proposed on the basis of optimization that indicate water discharge and pressure head when an additional pump should be switched on to ensure the highest total efficiency of the pump system.